How iron can drive neurodegeneration. Issue 5 (May 2023) - Kenkhuis, Boyd; Bush, Ashley I.; Ayton, Scott
Abstract: Iron overload in neurodegenerative diseases is well established but of uncertain significance. In a recent article, Ryan et al . reveal that microglia are especially vulnerable to iron overload-induced ferroptosis. Their evidence for microglial ferroptosis in clinical specimens indicates that ferroptosis inhibitors may hold therapeutic promise for these diseases.